2017
DOI: 10.12973/eurasia.2017.00607a
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Open and Technology Leadership in Managerial Practices of Education System

Abstract: In order for a smooth and problem-free transformation to take place in a digitalizing education system, efficient management is needed. Thus, educational managers need to improve their skills and develop behaviors suitable for taking education systems into the digital age. Social networks enable leaders to become digital citizens by embracing and implementing "Open Leadership". Acceptance of technology and self-efficacy in technological leadership are both seen as factors that can have positive or negative inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 13 publications
0
17
0
1
Order By: Relevance
“…Cluster 1 consists of studies focussed on leadership from the perspective of formal leaders: faculty governance (Ciabocchi, Ginsberg, & Picciano, 2016), university administrators (Livingstone, 2015;Spackman, Thorup, & Howell, 2015), senior leaders (Akcil, Aksal, Mukhametzyanova, & Gazi, 2017;Holt, Palmer, Gosper, Sankey, & Allan, 2015), online education administrators (Burnette, 2015) or through the mobilisation of local and international experts (Davis & Higgins, 2015;Díaz & Báez, 2015).…”
Section: Empirical Studies 2013-2017mentioning
confidence: 99%
See 1 more Smart Citation
“…Cluster 1 consists of studies focussed on leadership from the perspective of formal leaders: faculty governance (Ciabocchi, Ginsberg, & Picciano, 2016), university administrators (Livingstone, 2015;Spackman, Thorup, & Howell, 2015), senior leaders (Akcil, Aksal, Mukhametzyanova, & Gazi, 2017;Holt, Palmer, Gosper, Sankey, & Allan, 2015), online education administrators (Burnette, 2015) or through the mobilisation of local and international experts (Davis & Higgins, 2015;Díaz & Báez, 2015).…”
Section: Empirical Studies 2013-2017mentioning
confidence: 99%
“…-the application of technology acceptance and adoption models (Akcil et al, 2017;Boyd & Sampson, 2016;King & Boyatt, 2015;Livingstone, 2015;Markova, 2014;Sutton & DeSantis, 2017;Van Wart et al, 2017); -the application of tools and methods from the business world, as suggested by Sangrà (2009), with the caveat of the necessary cultural adaptation to HE (Chow, 2013;Mishra et al, 2016;Spackman et al, 2015;Tay & Low, 2017); -using data for decision-making (Brown et al, 2016;Burnette, 2015;Persichitte, 2013); -studying TEL adoption from the point of view of organisational learning (Tintoré & Arbós, 2013;Trevitt et al, 2017); -personal digital competence / literacy / confidence, of both leaders and staff (Akcil et al, 2017;Boyd & Sampson, 2016;Brown et al, 2016;DomingoCoscollola et al, 2016).…”
Section: Trendsmentioning
confidence: 99%
“…Administrators and teachers should quickly integrate technology into their management processes as 21st century communication tools rapidly develop and distribute information. The way to do this is to keep up with the digital age [22].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reveal the role of management and technology in the development of school cultures that they stay partial in facing the merits of information technology in conflict management (Altinay, Dagli, & Dagli, 2016;Aksal, A, 2016, Altinay, 2016. The study of Garcia-Valcarcel, Basilotta & Lopez (2014) encapsulates the role of collaborative learning in schools through the role of information technologies.…”
Section: Introductionmentioning
confidence: 99%